Impelementasi Program Parenting di Lembaga KB Al Baitul Amien Kelurahan Jember Lor Kecamatan Patrang Kabupaten Jember Tahun Pelajaran 2020/2021 - Fajar Abdillah; Husnul Khotimah (Program Studi Pendidikan Islam Anak Usia Dini Fakultas Tarbiyah Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2022)
Abstract: Family is one of the elements of the golden triangle of the education center or tri education center. Parents as representatives of the family have a very decisive role. The parenting program is the right solution in optimizing all educational processes in schools. The purpose of this study is to describe how the planning, implementation and evaluation of the Parenting Program at KB Al Baitul Amien. This research uses descriptive qualitative method. The technique of determining the informants in this study used purposive sampling. Data collection techniques using observation, interviews and documentation. Data analysis using Miles and Huberman. The results of this study indicate that the implementation of the parenting program at KB Al Baitul Amien is divided into 3 stages, namely, planning, implementation and evaluation stages. The planning stage includes the formation of a committee, determining learning needs, determining programs, determining facilities and infrastructure and arranging a schedule for implementing activities. The implementation stage of the parenting program includes the preparation stage for parenting program facilities and infrastructure, and the activity stage consisting of remarks, delivery of material by resource persons, followed by questions and answers then closed with conclusions and prayers. The evaluation stage uses the group discussion method. The components that are assessed are the process and the results.